Kedudukan Hukum Pemohon Perusahaan Swasta Dalam Permohonan PKPU Terhadap PT Persero di Indonesia (Analisis Putusan Nomor 425/PDT.Sus-Pkpu/2021/PN.Niaga.JKT.PST) - Ginting, Jamin; Hernico, Brenda (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Suspension of Payment (PKPU) is a legal mechanism allowing debtors to propose a peace agreement with creditors before being declared bankrupt, as regulated in Article 2 of Law No. 37 of 2004 on Bankruptcy and Suspension of Payment. However, discrepancies arise when PKPU applications from private companies against PT. Persero conflict with Article 2 paragraph (5), which requires certain BUMNs to have applications filed by the Minister of Finance. In the case of PKPU No. 425/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst, PT Mitra Buana Koorporindo’s application against PT Garuda Indonesia (Persero) Tbk was granted, highlighting legal uncertainty for private creditors unable to submit similar claims. This research aims to examine the judge's considerations and the legal standing of private PKPU applicants against PT. Persero under the Bankruptcy Law. Using a normative-empirical method, supported by case studies and interviews, the study finds that classifications of PKPU applicants are detailed in the Bankruptcy Law but often cause confusion in practice. The findings reveal that the current regulations do not sufficiently protect private creditors' rights. Nevertheless, in PKPU case No. 425/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst, the application was deemed compliant with the Bankruptcy Law, allowing private creditors to pursue claims against PT. Persero.